Crazy ants craving calcium: macronutrients and micronutrients can limit and stress an invaded grassland brown food web. Issue 2 (11th January 2021) - Reihart, Ryan W.; Angelos, Kiersten P.; Gawkins, Kaitlin M.; Hurst, Shania E.; Montelongo, Denise C.; Laws, Angela N.; Pennings, Steven C.; Prather, Chelse M.
Abstract: Nitrogen and phosphorus are thought to be the most important limiting nutrients in most terrestrial ecosystems, but little is known about how other elements may limit the abundance of arthropods. We utilized a fully factorial fertilization experiment that manipulated macronutrients (N and P, together) and micronutrients (calcium, sodium, potassium, separately), in large 30 × 30 m plots and sampled litter arthropods via pitfall trapping to determine the nutrients that limit this group. An invasive ant, Nylanderia fulva, numerically dominated the community and increased in abundance 13% in plots fertilized by Ca. Detritivores were not limited by any nutrient combination, but macronutrients increased predator abundance 43%. We also found that some combinations of macronutrients and micronutrients had toxic or stressful effects on the arthropod community: detritivores decreased in abundance 23% with the combination of macronutrients, Ca, and K, and 22% with macronutrients and K; and N. fulva decreased in abundance 24% in plots fertilized by K and 45% in plots fertilized by the combination of Na and K. Our work supports growing evidence that micronutrients, especially Ca and K, may be important in structuring grassland arthropod communities, and suggests that micronutrients may affect whether or not invasive ants reach numerical dominance.